PENGARUH KESEHATAN DAN KESELAMATAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN DI CV.PANDU PALAGAN SAMARINDA - -, Yeremias Lamahoda (EKONOMIA, 2014)
The purpose of this study is to determine how much influence the health of the employee's productivity CV. Pandu Theater amarinda. The number of members of a population of 34 employees. The sampling technique using simple random sampling because sampling is done at random members of the population without regard to existing strata in the population. And determining the sample size in this study using Slovin formula, in order to obtain the results as much as 20 respondents to be sampled in the study. This study used a descriptive analysis with quantitative approach using a questionnaire as a data collection tool and using simple linear regression analysis technique to measure the effect of independent variables on the dependent variable is the occupational health as an independent variable (X) and employee productivity as the dependent variable (Y). Processing of the data in this study is assisted by program Stastitical for Product and Service Solutions (SPSS) version 16. The benefits of this research was to determine the effect fariabel health programs on employee productivity in the CV. Pandu Theater Samarinda.Basic theory used is the operational management relating to the health and productivity of employees. The method used in this study adalan quantitative and descriptive nature of this study is an explanation. The method of data collection is done by interviews, questionnaires and documentation. Analysis of data using simple linear regression. Based on the analysis and discussion of the research CONCLUSIONS are: Formed regression function: Y = 0,0,135 + 0,786XThe results of this study stated that occupational health significant and positive impact on the productivity of employees CV. Pandu Theater Samarinda. Based on the results of an empirical test of occupational health variable has a value of coefficient of 0.786 with a t value 3.510 and significant value of 0.002. Thus the hypothesis that the existence of significant influence of occupational health programs on employee productivity CV. Pandu accepted Theater